Two-dimensional metal-organic framework thin film composite film and preparation method and application thereof
Through the suction filtration assisted-interface polymerization strategy, a ZIF-L/thin-layer composite film with high permeability and good separation effect was prepared, which solved the difficulty of 2D-MOF crystals to peel into stable nano-thickness two-dimensional nanosheets and PA layers and PA layers. The problem of poor interface compatibility achieves efficient dye/salt separation performance.
Patent Information
- Application Number
- CN202410679608.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-02-18
AI Technical Summary
The 2D-MOF crystals are difficult to peel into two-dimensional nanosheets with stable nano-thickness and have interfacial compatibility problems with the PA layer during interfacial polymerization, limiting the application of the preparation of TFC films with high water flux and dye/salt retention.
Through the suction filtration assisted-interface polymerization strategy, a ZIF-L/thin-layer composite film with good dye/salt separation performance was prepared. Using the chelation between partially exposed Zn2+ sites and amine monomers on the interface of ZIF-L nanosheets, the organic binding and uniform and stable dispersion of ZIF-L and aqueous monomers are achieved, and the interface between ZIF-L and PA layer is solved. Compatibility issues.
The prepared two-dimensional metal-organic framework thin film composite film has high permeability and good separation effect, with the Congo red retention rate of 99.99%, the Na2SO4 retention rate is 9.59%, and the CR/Na2SO4 selection ratio is 10.91.
Smart Images

Figure CN119455693A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of MOF membranes, and in particular relates to a two-dimensional metal-organic framework thin film composite membrane and a preparation method and application thereof. Background Art
[0002] In the membrane application process, membrane materials with good dye / salt rejection rate and high water flux are the core of membrane separation technology, which determines the selective permeability, process design, membrane stability and the final membrane separation applicable system. Thin film composite membrane (TFC) is prepared by interfacial polymerization (IP) reaction of cycloaliphatic polyamide and fully aromatic polyamide (such as piperazine) or aromatic diamine (such as m-phenylenediamine, MPD) with multifunctional aromatic acid chloride (mainly benzyl chloride, TMC). Since TFC membrane has high permeation flux and selectivity while maintaining sufficient mechanical strength, it has become a widely used high-performance separation membrane design.
[0003] Metal-organic frameworks (MOFs) are crystalline porous materials with periodic network structures formed by self-assembly of metal ions and organic ligands. In recent years, MOFs have attracted great interest in the manufacture of TFC membranes with excellent permeability selectivity. MOFs play a leading role in the separation process of membranes due to their various advantages of high porosity and regular pore size. The ideal modified MOF TFC membrane should have good stability in water, moderate particle size, suitable window size and high hydrophilicity.
[0004] In the existing MOF membrane preparation process, the introduction of MOF nanoparticles (i.e., ZIF-8, UiO-66-NH2, and CuBTC) into the membrane preparation process can improve the antifouling and permeability of MOF reverse osmosis membranes. However, 3D-MOF usually exhibits a blocky crystal morphology with a three-dimensional skeleton structure. The addition of 3D-MOF in interfacial polymerization may lead to the accumulation of MOFs in the selective layer, reducing the permeability of the membrane and the rejection of NaCl.
[0005] Two-dimensional MOF (2D-MOF) is a new type of MOF material. Due to its significant and large specific surface area, tunable structure and adjustable pore size, 2D-MOF has aroused great interest in the field of membrane manufacturing. In particular, the exfoliated 2D-MOF nanosheets have ultra-thin thickness and rich functional groups, which can significantly reduce the mass transfer resistance of water molecules and improve the performance of the membrane. Although 2D-MOF nanosheets have many advantages, there are few reports on TFN membranes based on 2D-MOF. This is mainly because 2D-MOF crystals are difficult to exfoliate into stable nano-thick two-dimensional nanosheets and there are interfacial compatibility issues with the polyamide (PA) layer in interfacial polymerization, which limits the application of preparing TFC membranes with high water flux and dye / salt rejection. Summary of the invention
[0006] In order to overcome the technical problems in the related art that 2D-MOF crystals are difficult to peel off into two-dimensional nanosheets with stable nanometer thickness and there is interface compatibility with the PA layer in interfacial polymerization, the present application provides a two-dimensional metal-organic skeleton thin film composite membrane and its preparation method and application. The preparation method has a simple preparation process and obviously solves the problems of ultra-thin preparation and interface compatibility of nanosheets, thereby obtaining a continuous and defect-free two-dimensional metal-organic skeleton thin film composite membrane.
[0007] The present invention provides a method for preparing a two-dimensional metal-organic skeleton thin film composite film, comprising the following steps:
[0008] S1. Dispersing ZIF-L nanosheets into an aqueous solution containing m-phenylenediamine (MPD), camphor-10-sulfonic acid and triethylamine (TEA) to obtain a MOF aqueous monomer solution;
[0009] S2. adding trimesoyl chloride (TMC) to n-hexane reagent to obtain an organic phase monomer solution;
[0010] S3. injecting the MOF aqueous monomer solution from the smooth surface of the wet PES ultrafiltration membrane, and simultaneously performing suction on the other side of the PES ultrafiltration membrane, after the aqueous solution in the MOF aqueous monomer solution is removed through the PES ultrafiltration membrane, injecting the organic monomer solution, reacting for 3-6 minutes, stopping suction and removing excess organic monomer solution;
[0011] S4. Dry the film obtained in step S3 at 60°C-80°C for 10-15 minutes to obtain a two-dimensional metal-organic framework thin film composite membrane.
[0012] Furthermore, the preparation method of ZIF-L nanosheets is as follows: zinc chloride is added to deionized water and stirred evenly to obtain a metal aqueous solution, 2-methylimidazole is added to deionized water and stirred evenly to obtain a ligand aqueous solution, the metal aqueous solution is poured into the ligand aqueous solution, mixed evenly and stirred to react, to obtain ZIF-L nanosheets.
[0013] Furthermore, in the preparation method of ZIF-L nanosheets, the concentration of zinc chloride in the metal aqueous solution is (2.5-4) g / ml; the concentration of 2-methylimidazole in the ligand aqueous solution is (2-3) g / ml; and the mass ratio of zinc chloride to 2-methylimidazole is (5-8):(4-6).
[0014] Furthermore, in the above-mentioned method for preparing the two-dimensional metal-organic framework thin film composite membrane, step S3 is specifically:
[0015] S31. The smooth surface of the wet PES ultrafiltration membrane soaked in deionized water is fixed upward on the filtration device, and the filtration pump below the PES ultrafiltration membrane is turned on for suction;
[0016] S32. After the excess water on the surface of the PES ultrafiltration membrane is sucked away, pour the MOF aqueous monomer solution from above. After the solution in the MOF aqueous monomer solution is removed through the PES ultrafiltration membrane, quickly pour the organic monomer solution on the surface of the PES ultrafiltration membrane. Under the suction force of the suction pump, react for 3-6 minutes, turn off the suction pump, and pour out the excess organic monomer solution.
[0017] Furthermore, in the above method for preparing the two-dimensional metal-organic framework thin film composite membrane, step S3 is performed in a constant temperature and humidity chamber at a temperature of 30° C. and a humidity of 40%.
[0018] Furthermore, in the preparation method of the above-mentioned two-dimensional metal-organic framework thin film composite membrane, in the MOF aqueous phase monomer solution, the concentration of ZIF-L nanosheets is 0.2-0.6wt%, and the concentration of MPD is 1.5-2.5wt%; in the organic phase monomer solution, the concentration of trimesoyl chloride is 0.1-0.5wt%; and the volume ratio of the MOF aqueous phase monomer solution to the organic phase monomer solution is 1:1.
[0019] Furthermore, in the above-mentioned method for preparing the two-dimensional metal-organic framework thin film composite membrane, in step S4, the drying is: drying in a vacuum oven.
[0020] The present invention also provides a two-dimensional metal-organic skeleton thin film composite membrane prepared by the above-mentioned preparation method.
[0021] The present invention also provides an application of the above-mentioned two-dimensional metal-organic skeleton thin film composite membrane in the treatment of textile printing and dyeing wastewater.
[0022] Compared with the prior art, the present invention prepares a ZIF-L / thin layer composite membrane with good dye / salt separation performance by using the suction filtration-assisted interfacial polymerization strategy. 2+ The chelation between the sites and the amine monomers achieves the organic combination of ZIF-L and the aqueous monomers and their uniform and stable dispersion, effectively solving the interfacial compatibility problem between ZIF-L and the PA layer. The aqueous solution is quickly sucked away by suction filtration while the organic monomers are quickly injected, inducing the organic monomers to penetrate into the gaps between the ZIF-L layers and react rapidly with the aqueous monomers wandering or adsorbed around the ZIF-L nanosheets, achieving interfacial polymerization reactions that penetrate into the bulk phase of the ZIF-L layer, resulting in the new PA layer perfectly coating the ZIF-L nanosheets. The permeability of the prepared two-dimensional metal-organic framework thin film composite membrane (ZIF / TFC membrane) is 1003.48L / m 2 ·h·bar, and has a good separation effect, among which the Congo red retention rate is 99.99%, the Na2SO4 retention rate is 9.59%, and the CR / Na2SO4 selectivity is 10.91. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The structure and morphology characterization diagram of ZIF-L nanosheets, including (a) XRD spectrum of ZIF-L nanosheets; (b) FTIR spectrum of ZIF-L nanosheets, (c) pore size distribution and specific surface area of ZIF-L nanosheets; (d) SEM image of ZIF-L nanosheets at high magnification; (e) AFM image of ZIF-L nanosheets and (f) thickness curve of ZIF-L nanosheets;
[0024] Figure 2 is a picture of ZIF / TFC-1 membrane; among them, Figure 2 -(1) and Figure 2 -(2) is the surface SEM image at different magnifications, Figure 2 -(3) is the cross-sectional SEM morphology image, Figure 2 -(4) is the AFM image;
[0025] Figure 3 is a picture of ZIF / TFC-2 membrane; among them, Figure 3 -(1) and Figure 3 -(2) is the surface SEM image at different magnifications, Figure 3 -(3) is the cross-sectional SEM morphology image, Figure 3 -(4) is the AFM image;
[0026] Figure 4is a picture of ZIF / TFC-4 membrane; among them, Figure 4 -(1) and Figure 4 -(2) is the surface SEM image at different magnifications, Figure 4 -(3) is the cross-sectional SEM morphology image, Figure 4 -(4) is the AFM image;
[0027] Figure 5 is a picture of ZIF / TFC-5 membrane; among them, Figure 5 -(1) and Figure 5 -(2) is the surface SEM image at different magnifications, Figure 5 -(3) is the cross-sectional SEM morphology image, Figure 5 -(4) is the AFM image;
[0028] Figure 6 is a picture of ZIF / TFC-6 membrane; among them, Figure 6 -(1) and Figure 6 -(2) is the surface SEM image at different magnifications, Figure 6 -(3) is the cross-sectional SEM morphology image, Figure 6 -(4) is the AFM image;
[0029] Figure 7 Characterization of the structure and morphology of the PA membrane: (a) SEM image of the surface of the PA membrane at high magnification; (b) SEM image of the surface of the PA membrane at low magnification; (c) SEM morphology of the cross section of the PA membrane and (d) AFM image;
[0030] Figure 8 The separation performances of ZIF / TFC-1, ZIF / TFC-2 and ZIF / TFC-4 membranes prepared in Example 2, Example 3 and Example 4 are as follows: (a) and (b) water permeation and retention rate for Congo red, methyl orange, methyl green and methylene blue; (c) and (d) water permeation and retention rate for NaCl, Na2SO4, MgCl2 and MgSO4;
[0031] Fig. 9 The performance stability of the ZIF / TFC-2 membrane prepared in Example 3; (a) the stability of membrane water permeation under different pressures, (b) the long-term stability of the Congo red separation performance of the ZIF / TFC-2 membrane, (c) the long-term stability of the Na2SO4 separation performance of the ZIF / TFC-2 membrane;
[0032] Fig.10The anti-fouling performance of the ZIF / TFC-2 membrane prepared in Example 3; (a) the anti-fouling performance of the ZIF / TFC-2 membrane to BSA and HA, (b) the time stability of the permeability and dye retention rate of the ZIF / TFC-2 membrane in an intermittent test (using Congo red solution for 2 hours and washing with water for 1 hour per cycle);
[0033] Fig.11 The separation properties of ZIF / TFC-5 and ZIF / TFC-6 membranes prepared in Examples 5 and 6 are as follows: (a) and (b) water permeance and retention rate for Congo red, methyl orange, methyl green and methylene blue; (c) and (d) water permeance and retention rate for NaCl, Na2SO4, MgCl2 and MgSO4. DETAILED DESCRIPTION
[0034] The present application is further described in detail below with reference to the accompanying drawings and specific embodiments, but the present application is not limited thereto.
[0035] The models and manufacturers of the instruments used in the various embodiments of this application are as follows:
[0036] Field emission electron scanning microscope (SEM), model: Drop Shape Analyzer 100, manufactured by Bruker, Germany;
[0037] Atomic force microscope (AFM), model: Tensor II, produced by Hitachi, Japan;
[0038] Specific surface area and porosity analyzer (BET), model: Micromeritics, ASAP 2020PlusHD88, produced by Micromeritics, USA;
[0039] X-ray diffraction (XRD), model: D2 Discover diffractometer, produced by Bruker, Germany;
[0040] Fourier transform infrared spectrometer (FTIR), model: ALPHAII, manufactured by Bruker, Germany
[0041] The permeation rate measuring instrument is a nanofiltration instrument, the model of which is (HP7890, Porapak N), produced by Agilent Technologies, USA;
[0042] The specifications and manufacturers of various raw materials used in the examples of this application are all commercially available except for the following special instructions:
[0043] Metaphenylenediamine (MPD) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0044] Camphor-10-sulfonic acid was purchased from Sane Chemical Technology Co., Ltd.;
[0045] Triethylamine (TEA) was purchased from MacLean Biochemical Technology Co., Ltd.;
[0046] n-Hexane, specification 99%, purchased from Aladdin Reagent Co., Ltd.;
[0047] The specification of trimesoyl chloride was 98%, and all were purchased from San Chemical Technology Co., Ltd.;
[0048] Polyethersulfone (PES) ultrafiltration membrane: average pore size 20-30 nm, provided by Zhongyi Filter Equipment Store, Zhouwangmiao Town, Haining City, soaked in deionized water for 6 hours before use;
[0049] Congo red, methyl orange, methyl green, and methylene blue were purchased from MacLean Biochemical Technology Co., Ltd.;
[0050] Sodium sulfate, magnesium sulfate, sodium chloride, and magnesium chloride were purchased from San Chemical Technology Co., Ltd.;
[0051] Zinc chloride: specification is 99%-Zn, purchased from McLean Biochemical Technology Co., Ltd.;
[0052] 2-Methylimidazole: Specification is 99%, purchased from McLean Biochemical Technology Co., Ltd.
[0053] Example 1 Preparation of two-dimensional ZIF-L nanosheets
[0054] 7.95 g of zinc chloride and 6.24 g of 2-methylimidazole were respectively added to 200 ml of deionized water and stirred evenly to obtain a metal solution and a ligand aqueous solution. The above-mentioned metal solution was then poured into the ligand aqueous solution and mixed and stirred evenly for 2 hours. After standing for 12 hours, it was centrifuged and washed with clean deionized water for 3 times, and placed in an 80°C forced air oven for drying for 10 hours to obtain a two-dimensional ZIF-L nanosheet.
[0055] The above ZIF-L nanosheets were tested by SEM, XRD, BET, and FTIR. The results are as follows: Figure 1 As shown, Figure 1 -a is the XRD spectrum of ZIF-L nanosheets. Compared with the XRD spectrum of ZIF-L nanosheets in the reference, the XRD peak of ZIF-L nanosheets is higher and has a good crystal structure. Figure 1 -b is the FTIR spectrum of ZIF-L nanosheets. Through the FTIR spectrum, we can find that 420.7cm -1 The peak is the Zn-N bond stretching vibration absorption peak, which verifies that the structure of the synthesized ZIF-L nanosheets is correct. Figure 1-c is the specific surface area and pore size distribution of ZIF-L nanosheets. The specific surface area of ZIF-L nanosheets is 18.56 m 2 / g, with a low specific surface area, which is conducive to giving full play to the performance of two-dimensional nanomaterials. In addition, the pore size of ZIF-L nanosheets is (1-d), (1-e) and (1-f) are the surface SEM image, cross-sectional SEM image and AFM image of ZIF-L nanosheets, respectively. The SEM and AFM image analysis show that the ZIF-L nanosheets synthesized by this method have a large aspect ratio, are thin and uniform, and have an average thickness of about 5 nm. The above tests indicate that the ZIF-L nanosheets prepared in this application are correct.
[0056] Example 2
[0057] (1) Preparation of ZIF-L-1 / aqueous monomer solution (MOF aqueous monomer solution)
[0058] 2 g of MPD, 2.4 g of camphor-10-sulfonic acid and 1.1 g of TEA were completely dissolved in 100 ml of deionized water as the aqueous phase, and stirred evenly in the dark. Then, 0.1 g of ZIF-L nanosheets were dispersed in the aqueous phase solution, stirred for 1 h, ultrasonicated for 15 min, and stirred for 2 h until completely dispersed, to obtain a ZIF-L-1 / aqueous phase monomer solution.
[0059] (2) Preparation of organic phase monomer solution
[0060] 0.2 g of TMC was added to 100 ml of pure n-hexane reagent and stirred at room temperature for 3 h to obtain an organic monomer solution.
[0061] (3) Preparation of ZIF / TFC-1 membrane
[0062] The wet PES ultrafiltration membrane soaked in deionized water was fixed on a suction filtration device with a clamp, with the front side (smooth side) of the membrane facing upward, and the suction pump was turned on to remove excess water from the membrane surface. Next, an aqueous monomer solution containing 0.1% ZIF-L nanosheets by mass was poured on the membrane surface, and then the excess aqueous monomer solution was extracted with a suction pump. Since the ZIF-L nanosheets were fully dispersed in the aqueous solution, the ZIF-L nanosheets would absorb part of the aqueous monomer containing amino groups due to the capillary action of the interlayers. Under the suction of the suction pump, most of the aqueous phase would enter and be adsorbed between the gaps of the ZIF-L nanosheet material. After the solution is removed, 0.2wt% of the organic phase solution is quickly poured onto the surface of the PES membrane. Under the action of suction force, the reaction lasts for 3 minutes, and the organic phase quickly enters the gaps between the ZIF-L nanosheets, thereby inducing an interfacial polymerization reaction around the ZIF-L nanosheet material. The aqueous phase monomers coated on the surface of the ZIF-L nanosheets can undergo a condensation reaction with the organic phase monomers, and then the excess organic phase solution is removed. The above operation is carried out in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40%.
[0063] The membrane was placed in a vacuum oven at 60°C and dried for 10 min to form a ZIF / TFC-1 membrane with embedded ZIF-L nanosheets.
[0064] The ZIF / TFC-1 membrane obtained above was scanned by SEM and AFM. The obtained SEM images are shown in Figure 2 As shown, Figure 2 -(1) and 2-(2) are SEM images of the membrane surface at 1 μm and 400 nm, respectively. Figure 2 -(3) is the SEM image of the film cross section at 10 μm; Figure 2 -(4) is the AFM image of the film at 1 μm. Figure 2 -(1) and 2-(2), it can be seen that when the mass fraction of ZIF-L nanosheets doped is 0.1wt%, the surface of the ZIF / TFC-1 membrane still retains the basic morphology of the pure PA membrane. Figure 2 -(3) shows that the thickness of the obtained ZIF / TFC-1 membrane is 3.22 μm. Figure 2 -(4) shows that the roughness of the obtained ZIF / TFC-1 membrane is 4.65 nm, which indicates that the ZIF / TFC-1 membrane prepared in Example 2 of the present invention is continuous and dense, and a large amount of basic morphology of PA membrane is retained on the membrane surface.
[0065] Example 3
[0066] (1) Preparation of ZIF-L-2 / aqueous monomer solution
[0067] 2 g of MPD, 2.4 g of camphor-10-sulfonic acid and 1.1 g of TEA were completely dissolved in 100 ml of deionized water as the aqueous phase, and stirred thoroughly in the dark. Then, 0.2 g of ZIF-L nanosheets were dispersed in the aqueous phase solution, stirred thoroughly for 1 hour, ultrasonicated for 15 minutes, and stirred for 2 hours until completely dispersed, to obtain a ZIF-L-2 / aqueous phase monomer solution;
[0068] (2) Preparation of organic phase monomer solution
[0069] Add 0.2 g of TMC into 100 ml of pure n-hexane reagent and stir thoroughly for 3 h at room temperature to obtain an organic monomer solution;
[0070] (3) Preparation of ZIF / TFC-2 membrane
[0071] The wet PES ultrafiltration membrane soaked in deionized water was fixed on a suction filtration device with a clamp (the front of the membrane was facing upward), and the suction pump was turned on to remove excess water from the membrane surface. Next, an aqueous monomer solution containing 0.2 wt% of ZIF-L nanosheets was poured on the membrane surface, and then the excess aqueous monomer solution was extracted with a suction pump. Since the ZIF-L nanosheets were fully dispersed in the aqueous solution, the ZIF-L nanosheets would absorb part of the aqueous monomer containing amino groups due to the capillary action of the interlayers. Under the suction of the suction pump, most of the aqueous phase would enter and be adsorbed between the gaps of the ZIF-L nanosheet material. After the solution is removed, 0.2wt% of the organic phase solution is quickly poured onto the surface of the PES membrane. Under the action of suction force, the reaction lasts for 3 minutes, and the organic phase quickly enters the gaps between the ZIF-L nanosheets, thereby inducing an interfacial polymerization reaction around the ZIF-L nanosheet material. The aqueous phase monomers coated on the surface of the ZIF-L nanosheets can undergo a condensation reaction with the organic phase monomers, and then the excess organic phase solution is removed. The above operation is carried out in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40%.
[0072] The ZIF / TFC-2 membrane obtained above was scanned by SEM and AFM. The obtained SEM images are shown in Figure 3 As shown, Figure 3 -(1) and 3-(2) are surface SEM images at 1 μm and 400 nm, respectively. Figure 3 -(3) is a cross-sectional SEM image at 10 μm; Figure 3 -(4) is the AFM image at 1 μm. Figure 3-(1) and 3-(2), it can be seen that when the mass fraction of ZIF-L nanosheets reaches 0.2wt%, the surface morphology of the ZIF / TFC-2 membrane changes significantly compared with the pure PA membrane. The leaf-like structure of the PA layer is short and not obvious, and the membrane surface becomes smoother. Figure 3 -(3) shows that the thickness of the obtained ZIF / TFC-2 membrane is 3.22 μm. Figure 3 -(4) shows that the roughness of the obtained ZIF / TFC-2 membrane is 1.08 nm, which indicates that the ZIF / TFC-2 membrane prepared in Example 3 of the present invention is continuous and dense, and the membrane surface is smoother.
[0073] Example 4
[0074] (1) Preparation of ZIF-L-4 / aqueous monomer solution
[0075] 2 g of MPD, 2.4 g of camphor-10-sulfonic acid and 1.1 g of TEA were completely dissolved in 100 ml of deionized water as the aqueous phase, and stirred thoroughly in the dark. Then, 0.4 g of ZIF-L nanosheets were dispersed in the aqueous phase solution, stirred thoroughly for 1 hour, ultrasonicated for 15 minutes, and continued to stir for 2 hours until completely dispersed, to obtain a ZIF-L-4 / aqueous phase monomer solution;
[0076] (2) Preparation of organic phase monomer solution
[0077] Add 0.2 g of TMC into 100 ml of pure n-hexane reagent and stir thoroughly for 3 h at room temperature to obtain an organic monomer solution;
[0078] (3) Preparation of ZIF / TFC-4 membrane
[0079] The wet PES ultrafiltration membrane soaked in deionized water was fixed on a suction filtration device with a clamp (the front of the membrane was facing upward), and the suction pump was turned on to remove excess water from the membrane surface. Next, an aqueous monomer solution containing 0.4 wt% of ZIF-L nanosheets was poured on the membrane surface, and then the excess aqueous monomer solution was extracted with a suction pump. Since the ZIF-L nanosheets were fully dispersed in the aqueous solution, the ZIF-L nanosheets would absorb part of the aqueous monomer containing amino groups due to the capillary action of the interlayers. Under the suction of the suction pump, most of the aqueous phase would enter and be adsorbed between the gaps of the ZIF-L nanosheet material. After the solution is removed, 0.2wt% of the organic phase solution is quickly poured onto the surface of the PES membrane. Under the action of suction force, the reaction lasts for 3 minutes, and the organic phase quickly enters the gaps between the ZIF-L nanosheets, thereby inducing an interfacial polymerization reaction around the ZIF-L nanosheet material. The aqueous phase monomers coated on the surface of the ZIF-L nanosheets can undergo a condensation reaction with the organic phase monomers. The excess organic phase solution is then removed, and the membrane is placed in a vacuum oven at 60°C and dried for 10 minutes to form a ZIF / TFC-4 membrane with embedded ZIF-L nanosheets. The above operation is performed in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40%.
[0080] The ZIF / TFC-4 membrane obtained above was scanned by SEM and AFM. The obtained SEM images are shown in Figure 4 As shown, Figure 4 -(1) and 4-(2) are SEM images of the membrane surface at 1 μm and 400 nm, respectively. Figure 4 -(3) is the SEM image of the film cross section at 10 μm; Figure 4 -(4) is the AFM image of the film at 1 μm. Figure 4 -(1) and 4-(2), it can be seen that when the mass fraction of ZIF-L nanosheets is 0.4wt%, the ZIF / TFC-4 membrane exhibits obvious ZIF-L nanosheet morphology, and nanoparticle-like protrusions are distributed on the surface. Figure 4 -(3) shows that the thickness of the obtained ZIF / TFC-4 membrane is 5.13 μm. Figure 4 -(4) shows that the roughness of the obtained ZIF / TFC-4 membrane is 8.68 nm. This shows that the ZIF / TFC-4 membrane prepared in Example 4 of the present invention has a high mass fraction of ZIF-L nanosheets, which makes the ZIF-L nanosheet structure prominent, and the PA layer is not enough to completely cover the nanosheets, and easily forms accumulation and defects on the membrane surface, which is not conducive to enhancing the flux and retention rate of the membrane.
[0081] Example 5
[0082] (1) Preparation of ZIF-L-2 / aqueous monomer solution
[0083] 2 g of MPD, 2.4 g of camphor-10-sulfonic acid and 1.1 g of TEA were completely dissolved in 100 ml of deionized water as the aqueous phase, and stirred thoroughly in the dark. Then, 0.2 g of ZIF-L nanosheets were dispersed in the aqueous phase solution, stirred thoroughly for 1 hour, ultrasonicated for 15 minutes, and stirred for 2 hours until completely dispersed, to obtain a ZIF-L-2 / aqueous phase monomer solution;
[0084] (2) Preparation of organic phase monomer solution
[0085] Add 0.1 g of TMC into 100 ml of pure n-hexane reagent and stir thoroughly for 3 h at room temperature to obtain an organic monomer solution;
[0086] (3) Preparation of ZIF / TFC-5 membrane
[0087] The wet PES ultrafiltration membrane soaked in deionized water was fixed on a suction filtration device with a clamp (the front of the membrane was facing upward), and the suction pump was turned on to remove excess water from the membrane surface. Next, an aqueous monomer solution containing 0.2 wt% of ZIF-L nanosheets was poured on the membrane surface, and then the excess aqueous monomer solution was extracted with a suction pump. Since the ZIF-L nanosheets were fully dispersed in the aqueous solution, the ZIF-L nanosheets would absorb part of the aqueous monomer containing amino groups due to the capillary action of the interlayers. Under the suction of the suction pump, most of the aqueous phase would enter and be adsorbed between the gaps of the ZIF-L nanosheet material. After the solution is removed, 0.1wt% of the organic phase solution is quickly poured onto the surface of the PES membrane. Under the action of suction force, the reaction lasts for 3 minutes, and the organic phase quickly enters the gaps between the ZIF-L nanosheets, thereby inducing an interfacial polymerization reaction around the ZIF-L nanosheet material. The aqueous phase monomers coated on the surface of the ZIF-L nanosheets can undergo a condensation reaction with the organic phase monomers. The excess organic phase solution is then removed, and the membrane is placed in a vacuum oven at 60°C and dried for 10 minutes to form a ZIF / TFC-5 membrane with embedded ZIF-L nanosheets. The above operation is performed in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40%.
[0088] The ZIF / TFC-5 membrane obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 5 As shown, Figure 5 -(1) and 5-(2) are plane scanning electron microscopy images at 1μm and 400nm, respectively. Figure 5 -(3) is a cross-sectional SEM image at 10 μm. Figure 5-(1) and 5-(2) show that when the mass fraction of TMC reaches 0.1wt%, the surface morphology of the ZIF / TFC-5 membrane changes significantly compared with the pure PA membrane. The leaf-like structure of the PA layer is short and not obvious, and the membrane surface has obvious ZIF-L nanosheet morphology. This is because when the TMC concentration is too low, the interfacial polymerization reaction with the aqueous phase monomer is poor, which leads to poor interfacial compatibility of the membrane, thus affecting the dye / salt separation performance of the membrane. Figure 5 -(3) shows that the thickness of the obtained ZIF / TFC-5 membrane is 4.21 μm, which indicates that the surface of the ZIF / TFC-5 membrane prepared in Example 5 of the present invention is smooth, but obvious stratification can be seen from the cross section, indicating that when the TMC concentration is too low, the interfacial compatibility of the membrane is poor, thereby affecting the separation performance of the membrane.
[0089] Example 6
[0090] (1) Preparation of ZIF-L-2 / aqueous monomer solution
[0091] 2 g of MPD, 2.4 g of camphor-10-sulfonic acid and 1.1 g of TEA were completely dissolved in 100 ml of deionized water as the aqueous phase, and stirred thoroughly in the dark. Then, 0.2 g of ZIF-L nanosheets were dispersed in the aqueous phase solution, stirred thoroughly for 1 hour, ultrasonicated for 15 minutes, and stirred for 2 hours until completely dispersed, to obtain a ZIF-L-2 / aqueous phase monomer solution;
[0092] (2) Preparation of organic phase monomer solution
[0093] Add 0.4 g of TMC into 100 ml of pure n-hexane reagent and stir thoroughly for 3 h at room temperature to obtain an organic monomer solution;
[0094] (3) Preparation of ZIF / TFC-6 membrane
[0095] The wet PES ultrafiltration membrane soaked in deionized water was fixed on a suction filtration device with a clamp (the front of the membrane was facing upward), and the suction pump was turned on to remove excess water from the membrane surface. Next, an aqueous monomer solution containing 0.2 wt% of ZIF-L nanosheets was poured on the membrane surface, and then the excess aqueous monomer solution was extracted with a suction pump. Since the ZIF-L nanosheets were fully dispersed in the aqueous solution, the ZIF-L nanosheets would absorb part of the aqueous monomer containing amino groups due to the capillary action of the interlayers. Under the suction of the suction pump, most of the aqueous phase would enter and be adsorbed between the gaps of the ZIF-L nanosheet material. After the solution is removed, 0.4wt% of the organic phase solution is quickly poured onto the surface of the PES membrane. Under the action of suction force, the reaction lasts for 3 minutes, and the organic phase quickly enters the gaps between the ZIF-L nanosheets, thereby inducing an interfacial polymerization reaction around the ZIF-L nanosheet material. The aqueous phase monomers coated on the surface of the ZIF-L nanosheets can undergo a condensation reaction with the organic phase monomers. The excess organic phase solution is then removed, and the membrane is placed in a vacuum oven at 60°C and dried for 10 minutes to form a ZIF / TFC-6 membrane with embedded ZIF-L nanosheets. The above operation is performed in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40%.
[0096] The ZIF / TFC-6 membrane obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 6 As shown, Figure 6 -(1) and 6-(2) are SEM images of the membrane surface at 1 μm and 400 nm, respectively. Figure 6 -(3) is a cross-sectional SEM image at 10 μm. Figure 6 -(1) and 6-(2), it can be seen that when the mass fraction of TMC reaches 0.4wt%, the surface morphology of the ZIF / TFC-6 membrane is not much different from that of the pure PA membrane, the leaf-like structure of the PA layer is still obvious, and the membrane thickness is significantly increased. Figure 6 -(3) shows that the thickness of the obtained ZIF / TFC-6 membrane is 4.75 μm. This shows that the prepared ZIF / TFC-6 membrane of Example 6 of the present invention is continuous and dense and has an obvious lotus leaf shape on the membrane surface, but the TMC concentration is too high, which significantly increases the membrane density and thus significantly reduces the water flux of the membrane.
[0097] Example 7
[0098] (1) Preparation of pure aqueous monomer solution
[0099] 2 g of MPD, 2.4 g of camphor-10-sulfonic acid and 1.1 g of TEA were completely dissolved in 100 ml of deionized water as the aqueous phase, and stirred for 1 h in the dark until completely dispersed to obtain a pure aqueous monomer solution;
[0100] (3) Preparation of organic phase monomer solution
[0101] 0.2 g of TMC was added to 100 ml of pure n-hexane reagent and stirred for 3 hours at room temperature to obtain an organic monomer solution;
[0102] (4) Preparation of PA membrane
[0103] Fix the wet PES ultrafiltration membrane that has been soaked in deionized water in advance on a suction filtration device with a clamp (the front of the membrane faces upward), and turn on the suction pump to remove excess water from the membrane surface. Next, pour the pure aqueous monomer solution on the membrane surface, and then use the suction pump to extract the excess aqueous monomer solution. After the aqueous monomer solution is removed, quickly pour 0.2wt% of the organic phase solution on the surface of the PES membrane. Under the action of suction force, react for 3 minutes to induce interfacial polymerization reaction, then remove the excess organic phase solution, and place the membrane in a vacuum oven at 60°C to dry for 10 minutes to form a PA membrane. The above operations are carried out in a constant temperature and humidity chamber with a temperature of 30°C and a humidity of 40%.
[0104] The PA film obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 7 As shown, Figure 7 -a and 7-b are SEM images of the membrane surface at 1 μm and 400 nm, respectively. Figure 7 -c is a cross-sectional SEM image at 10 μm; Figure 7 -d is the AFM image of the film at 1 μm. Figure 7 -a and 7-b, it can be seen that there are obvious lotus leaf-like protrusions on the surface of the PA film. Figure 7 -c shows that the thickness of the PA film is 141.71 nm. Figure 7 -d, it can be seen that the roughness of the obtained PA film is 35.97 nm.
[0105] Test Case
[0106] Different types of ZIF / TFC membranes were cut into the same size as the test membrane pool area and placed in the membrane pool. The samples were pre-pressurized at 1 bar for 2 hours to achieve stability. Then, the permeation rate and retention rate of the membrane to different dyes and salt solutions were recorded at equal intervals. The average value was taken and the performance stability of the membrane was tested over a longer period of time.
[0107] Performance measurement method
[0108] For the determination method of dye / salt separation selectivity, see the literature Liu Y, Wang XP, Zong ZA, et al. Thin film nanocomposite membrane incorporated with 2D-MOF nanosheets for highly efficient reverse osmosis desalination [J]. Journal of Membrane Science, 2022, 653(5): 120520. The prepared nanofiltration membrane was tested for flux and retention rate using a cross-flow filtration device. The effective area of the test membrane pool was 7.06 cm 2 , the concentration of dye and salt was 100 ppm. The samples were pre-pressed at 1 bar for 2 hours to reach stable conditions. The permeability and retention of the membrane were measured within 20 min.
[0109] The membrane permeability (P) can be expressed by the formula Calculated:
[0110] Where V(L) is the volume of permeate passing through the membrane, A(m 2 ) is the effective area of the membrane being tested, t (h) is the test time, Δp (bar) is the transmembrane pressure during the test, and the unit of P is (L m -2 h -1 bar -1 ).
[0111] The dye concentration in the feed and permeate was determined by UV / visible spectroscopy (Shimadzu), and the salt concentration was determined by FE38 conductivity meter (Mettler Toledo). The concentration was calculated from the standard curves of dye and salt, according to the formula Calculate the retention rate (R%) of dye and salt:
[0112] Where CP is the permeate solution and Cf is the feed solution.
[0113] The water flux and dye / salt of the ZIF / TFC-1 membrane, ZIF / TFC-2 membrane and ZIF / TFC-4 membrane obtained in the above-mentioned Example 2, Example 3 and Example 4 were measured respectively. The measurement data results are shown in the following table:
[0114]
[0115] As can be seen from the table above, the ZIF / TFC-1 membrane, ZIF / TFC-2 membrane, and ZIF / TFC-4 membrane of the present invention separate dyes / salts, and their Congo red water flux cutoffs are 694.04 Lm -2 h -1bar -1 、1003.48Lm -2 h -1 bar -1 、907.33Lm -2 h -1 bar -1 The interception rates of Congo red were 97.89%, 99.99%, and 95.54%, respectively, and the interception flux of Na2SO4 was 524.54Lm -2 h -1 bar -1 、707.31Lm -2 h -1 bar -1 、652.21Lm -2 h -1 bar -1 , the Na2SO4 retention rates were 11.44%, 9.71% and 10.08% respectively.
[0116] The dye / salt separation selectivity performance data of the ZIF / TFC-1 membrane, ZIF / TFC-2 membrane, and ZIF / TFC-4 membrane obtained in Example 2, Example 3, and Example 4 are shown in FIG. Figure 8 As shown, from Figure 8 It can be further clearly seen that as the content of ZIF-L nanosheets doped in the membrane increases, the membrane separation selectivity also increases, which shows that the dye / salt separation performance of the MOF membrane obtained by the preparation method of the MOF membrane of the present application is significantly improved with the increase of ZIF-L nanosheets.
[0117] Based on the above results, under the premise of selecting CR dye as stock solution and Na2SO4 as stock solution, Fig. 9 (a) It further shows that with CR dye as the stock solution, the permeability of the ZIF / TFC-2 membrane increases with the increase of the test pressure, which can be increased from 1003.35Lm -2 h -1 bar -1 Increased to 1132.1Lm -2 h -1 bar -1 In addition, the stability of the permeability and rejection rate of the ZIF / TFC-2 membrane over time was tested using CR dye as the stock solution and Na2SO4 as the stock solution, respectively. Fig. 9(bc). The experimental results show that under the condition that other test conditions remain unchanged, as the test time increases, the water permeability and retention rate of the ZIF / TFC-2 membrane for dyes and salts decrease slightly in a short period of time, but remain relatively stable after a longer period of time. This is because the Congo red molecules on the surface of the membrane are enriched through dye adsorption and accumulation in the early stage, resulting in a decrease in the permeability of the membrane. However, since the dye molecules have good water solubility, the adsorption-desorption process is dynamic, and when equilibrium is reached, the permeability of the dye solution remains stable. Although the permeability of the membrane has decreased to a certain extent, the rejection reaction to the dye has hardly changed.
[0118] The anti-fouling performance of ZIF / TFC membrane was tested by using 0.1g / L BSA and HA solutions as pollutants. The permeability of ZIF / TFC-2 membrane decreased sharply before the BSA solution test, but after being rinsed with pure water, the permeability could be restored to 864.5Lm -2 h -1 bar -1 The water flux recovery rate after water washing was 86.5%, which basically maintained its original performance ( Fig.10 (a)); for the HA solution test, the membrane permeability can be restored to 904.2Lm -2 h -1 bar -1 . The water flux recovery rate after water washing was 90.3%. This may be due to the low roughness of the membrane and the small water contact angle of the membrane, which is not conducive to the attachment of pollutants on the membrane surface. The above experiments indirectly prove that BSA and HA did not penetrate into the membrane pores and only caused slight contamination on the membrane surface. Therefore, the ZIF / TFC membrane has a relatively high protection against BSA contamination. In addition, the membrane was intermittently tested for a long time (using Congo red solution for 2 hours and then washing for 1 hour each cycle). Fig.10 (b) shows that the membrane permeability is slightly reduced, and the dye molecule rejection is maintained at a high level, indicating that the ZIF / TFC membrane has good durability and long-term performance stability, which is conducive to the practical application of the membrane.
[0119] The water flux and dye / salt of the ZIF / TFC-5 membrane and ZIF / TFC-6 membrane obtained in the above-mentioned Example 5 and Example 6 were measured respectively. The measurement data results are shown in the following table:
[0120]
[0121]
[0122] As can be seen from the table above, the ZIF / TFC-5 membrane and ZIF / TFC-6 membrane of the present application are used to separate dyes / salts, and their Congo red water flux cutoffs are 1123.68 Lm -2 h -1 bar -1 、407.02Lm -2 h -1 bar -1 The interception rates of Congo red were 90.79% and 98.69%, respectively, and the interception flux of Na2SO4 was 938.16Lm -2 h -1 bar -1 、588.15Lm -2 h -1 bar -1 , the Na2SO4 retention rates were 24.69% and 14.96% respectively.
[0123] The dye / salt separation selectivity performance data of the ZIF / TFC-5 membrane and ZIF / TFC-6 membrane obtained in Example 5 and Example 6 are shown in FIG. Fig.11 As shown, from Fig.11 It can be further clearly seen that as the TMC concentration in the membrane increases, the membrane separation selectivity decreases significantly, which shows that the dye / salt separation performance of the MOF membrane obtained by the preparation method of the MOF membrane of the present application decreases due to the increase in the added TMC concentration.
[0124] In summary, the preparation method of a two-dimensional metal-organic framework thin film composite membrane of the present application is carried out at room temperature throughout the process. By controlling the mass fraction of the doped ZIF-L nanosheets and selecting the appropriate TMC concentration, the interfacial compatibility problem between the membrane and the substrate is improved, the uniform dispersion of 2D-MOF in the thin film composite membrane is achieved, and a continuous and dense two-dimensional MOF thin film composite membrane is prepared, which overcomes the technical problems of uneven distribution of MOFs in the membrane, difficulty in peeling 2D-MOF crystals into two-dimensional nanosheets with stable nanometer thickness, and poor interfacial compatibility with the PA layer in interfacial polymerization in the existing related technology. The surface of the MOF membrane finally obtained is dense, continuous and tightly bonded to the substrate, and the water flux of the Congo red dye is 694-1004GPU, the Congo red retention rate is 95.54%-99.99%, and the sodium sulfate retention rate is 9.61%-11.44%.
[0125] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a two-dimensional metal-organic framework thin film composite membrane, characterized in that: The following steps are involved: S1. dispersing ZIF-L nanosheets into an aqueous solution containing m-phenylenediamine, camphor-10-sulfonic acid and triethylamine to obtain a MOF aqueous monomer solution; S2. adding trimesoyl chloride to the n-hexane reagent to obtain an organic phase monomer solution; S3. The MOF aqueous monomer solution is injected from the smooth surface of the wet PES ultrafiltration membrane, and suction is performed on the other side of the PES ultrafiltration membrane. After the solution in the MOF aqueous monomer solution is removed through the PES ultrafiltration membrane, the organic monomer solution is quickly injected. After reacting for 3-6 minutes, suction is stopped and excess organic monomer solution is removed; S4. Dry the film obtained in step S3 at 60°C-80°C for 10-15 minutes to obtain a two-dimensional metal-organic framework thin film composite membrane.
2. The preparation method according to claim 1, characterized in that: The preparation method of the ZIF-L nanosheet is as follows: zinc chloride is added to deionized water and stirred evenly to obtain a metal aqueous solution, 2-methylimidazole is added to deionized water and stirred evenly to obtain a ligand aqueous solution, the metal aqueous solution is poured into the ligand aqueous solution, mixed evenly and stirred for reaction to obtain the ZIF-L nanosheet.
3. The preparation method according to claim 2, characterized in that: In the preparation method of the ZIF-L nanosheets, the concentration of zinc chloride in the metal aqueous solution is (2.5-4) g / ml; the concentration of 2-methylimidazole in the ligand aqueous solution is (2-3) g / ml; and the mass ratio of zinc chloride to 2-methylimidazole is (5-8):(4-6).
4. The preparation method according to claim 1, characterized in that: Step S3 is specifically as follows: S31. The smooth surface of the wet PES ultrafiltration membrane soaked in deionized water is fixed upward on the filtration device, and the filtration pump located below the PES ultrafiltration membrane is turned on for suction; S32. After the excess water on the surface of the PES ultrafiltration membrane is sucked away, pour the MOF aqueous monomer solution from the top, and after the solution in the MOF aqueous monomer solution is removed through the PES ultrafiltration membrane, quickly pour the organic monomer solution on the surface of the PES ultrafiltration membrane, react for 3-6 minutes under the suction force of the suction pump, turn off the suction pump and remove the excess organic monomer solution.
5. The preparation method according to claim 1, characterized in that: Step S3 is performed in a constant temperature and humidity chamber at a temperature of 30° C. and a humidity of 40%.
6. The preparation method according to claim 1, characterized in that: In the MOF aqueous monomer solution, the concentration of ZIF-L nanosheets is 0.2-0.6wt%, and the concentration of MPD is 1.5-2.5wt%; in the organic monomer solution, the concentration of trimesoyl chloride is 0.1-0.5wt%; and the volume ratio of the MOF aqueous monomer solution to the organic monomer solution is 1:
1.
7. The preparation method according to claim 1, characterized in that: In step S4, the drying is: drying in a vacuum oven.
8. A two-dimensional metal-organic skeleton thin film composite membrane prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the two-dimensional metal-organic skeleton thin film composite membrane according to claim 8 in the treatment of textile printing and dyeing wastewater.
Citation Information
Cited By
Conductive nanofiltration membrane, roll type conductive membrane filter element and nanofiltration separation method
CN121060321A
A conductive nanofiltration membrane, a conductive membrane filter cartridge and a nanofiltration separation method
CN121060321B
Anti-pollution nanofiltration membrane based on molecular suture-interfacial polymerization strategy as well as preparation method and application of anti-pollution nanofiltration membrane
CN121243995A
Polyamide composite membrane and preparation method thereof
CN121288588A